Shrubs and trees of the Colombian Amazonian foothills: Nutritional and environmental potential in livestock systems - Narváez-Herrera, Juan Pablo; Angulo-Arizala, Joaquín; Barragán-Hernández, Wilson; Mahecha-Ledesma, Liliana (Agronomía Mesoamericana, 2023)
Introduction. The Amazon foothills livestock is characterized by inefficient land use, pasture monoculture, and significant reduction of the forest, which added to greenhouse gas emissions; it correlates the livestock practices to climate change. Objective. To compile and analyze research on Erythrina poeppigiana (Walp.) O.F. Cook, Clitoria fairchildiana R.A. Howard, Piptocoma discolor (Kunth) Pruski and Guazuma ulmifolia Lam. Development. Through the use of Google Scholar, search algorithms, and keywords 97 papers related to this study were found and analyzed . To the forage shrubs of interest, the review reported a wide environmental range of adaptation (0 - 1600 m a. s. l. and between 1000 and 3700 mm rain/year), with the potential to develop in poorly drained soils and with low pH. The use of these shrubs in livestock was related to living fences, fodder banks, and direct intake, among others. Likewise, the literature review reported a dry matter concentration between 23 and 35 %, crude protein between 15 % and 21 %, and NDF and ADF <60 % and <45 %, respectively. Additionally, reports of secondary plant metabolites like tannins and saponins were also found, which could be related to the reduction of enteric methane. Lastly, the review examines the potential effect on carbon storage and land restoration by including the shrubs species discussed in the present study due to the possible effect on nitrogen fixation (legumes) and soil nutrient restoration via litter decomposition. Conclusions. Due to their nutritional characteristics, wide range of adaptation, and phytochemical profile, it would be pertinent to evaluate the behavior of the species E. poeppigiana, C. fairchildiana, P. discolor, and G. ulmifolia, as a strategy to improve nutrition and reduce methane emission in the Amazon foothills livestock farming.